Spontaneous Regression of Ovarian Carcinoma After Septic Peritonitis; A Unique Case Report - Roelofsen, Thijs; Wefers, Christina; Gorris, Mark A. J.; Textor, Johannes C.; Massuger, Leon F. A. G.; de Vries, I. Jolanda M.; van Altena, Anne M. (Frontiers in Oncology, 2018)
Despite advances in therapy, ovarian cancer remains the most lethal gynecological malignancy and prognosis has not substantially improved over the past 3 decades. Immunotherapy is a promising new treatment option. However, the immunosuppressive cancer microenvironment must be overcome for immunotherapy to be successful. Here, we present a unique case of spontaneous regression of ovarian carcinoma after septic peritonitis. A 79-year-old woman was diagnosed with stage IIIc ovarian cancer. The omental cake biopsy was complicated by sepsis. Although the patient recovered, her physical condition did not allow further treatment for her ovarian cancer. After six months, spontaneous regression of the tumor was observed during surgery. Analysis of the immune infiltrate in the tissues showed a shift from a pro-tumorigenic to an anti-tumorigenic immune response after sepsis. Strong activation of the immune system during sepsis overruled the immunosuppressive tumor microenvironment and allowed for a potent anti-tumor immune response. More understanding of immunological responses in cases with cancer and septic peritonitis might be crucial to identify potential new targets for immunotherapy.